2018
DOI: 10.1007/s10493-018-0299-y
|View full text |Cite
|
Sign up to set email alerts
|

Acaricidal properties of ylang-ylang oil and star anise oil against nymphs of Ixodes ricinus (Acari: Ixodidae)

Abstract: Ylang-ylang oil (YYO) from Cananga odorata (Lam.) Hook.f. & Thomson and star anise oil (SAO) from Illicium verum Hook.f. were tested at four concentrations 0.05, 0.1, 0.2, 0.4 µl/cm 2. Mortality rates were obtained by counting dead nymphs at 30-min intervals during the first 5 h after the start of exposure and then at 24, 48 and 72 h. Mortality increased with increasing oil concentration and time of exposure. The two highest concentrations of YYO (0.2, 0.4 µl/cm 2) gave maximum lethal concentrations (LC) of 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Its essential oil has insecticidal activity for larvae (LC 50 = 39.8 µg.mL -1 ) and adults (LC 50 = 10.3 µg.mg.female -1 ) of Aedes aegypti (Gomes da Rocha Voris et al, 2018) and against the insect of importance for grain storage Tribolium confusum (LC 50 = 552 µl.L -1 ) (Popović et al, 2019). Acaricide activity has also been described for environmental mites Dermatophagoides pteronyssinus (LC 50 = 0.032 µg.cm -2 ) (Nilprapat et al, 2017) and tick nymph Ixodes ricinus (LC 50 = 0.2 µl.cm -2 ) (Elmhalli et al, 2018). Added to the results obtained in this study, star anise essential oil demonstrates to be able to act against different classes of arthropods, hematophagous or not, making it promising for the development of an ectoparasiticidal formulation.…”
Section: Discussionmentioning
confidence: 92%
“…Its essential oil has insecticidal activity for larvae (LC 50 = 39.8 µg.mL -1 ) and adults (LC 50 = 10.3 µg.mg.female -1 ) of Aedes aegypti (Gomes da Rocha Voris et al, 2018) and against the insect of importance for grain storage Tribolium confusum (LC 50 = 552 µl.L -1 ) (Popović et al, 2019). Acaricide activity has also been described for environmental mites Dermatophagoides pteronyssinus (LC 50 = 0.032 µg.cm -2 ) (Nilprapat et al, 2017) and tick nymph Ixodes ricinus (LC 50 = 0.2 µl.cm -2 ) (Elmhalli et al, 2018). Added to the results obtained in this study, star anise essential oil demonstrates to be able to act against different classes of arthropods, hematophagous or not, making it promising for the development of an ectoparasiticidal formulation.…”
Section: Discussionmentioning
confidence: 92%
“…As reported by Gomes da Rocha Voris et al [78] and Popović et al [79], the EO derived from this plant demonstrates insecticidal effects against Aedes aegypti larvae and adults, as well as against the insect Tribolium confusum, thereby contributing to the preservation of grains. The environmental mites Dermatophagoides pteronyssinus [80] and the tick nymph Ixodes ricinus [81] have also been reported to have acaricide activity. In addition to the findings of this investigation, star anise essential oil shows promise in the fight against H. axyridis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the management of crop pests, P. anisum oil had an excellent performance on larval elimination and cutting-off transmission against pests spreading epidemic diseases. Numerous studies have provided convictive evidence of larval killing and oviposition deterrent activities of P. anisum on pestiferous pests, the vector of dengue, human African trypanosomiasis, and filariasis [ 48 , 136 , 137 , 138 , 139 , 140 ]. A. T. Showler et al further demonstrated p -anisaldehyde was a botanical ingredient inhibiting the reproduction of pests [ 139 , 140 ].…”
Section: Pharmacologymentioning
confidence: 99%